2013
DOI: 10.1118/1.4813303
|View full text |Cite
|
Sign up to set email alerts
|

Heel effect adaptive flat field correction of digital x-ray detectors

Abstract: The Duo-SID correction method has substantially improved on conventional offset/gain corrections for digital x-ray imaging in an SID-variant environment. The technique is relatively simple, and can be easily incorporated into multiple-point gain calibration/correction techniques. It offers a potentially valuable tool for preprocessing digital x-ray images to boost image quality of mammography, chest and cardiac radiography, as well as automated computer aided diagnostic radiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…In radiography, the heel effect causes less X-ray fluence and higher mean radiation energy in the anode direction, and results in non-uniform image quality. Although there have been some methods proposed to reduce the heel effect [ 19 , 20 , 21 ], no suitable method has been presented that can objectively quantify the overall and non-uniform image quality caused by the heel effect. This study designed a CSW phantom for quantification of overall and non-uniform image quality in X-ray radiographs using nMI metrics based on information theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In radiography, the heel effect causes less X-ray fluence and higher mean radiation energy in the anode direction, and results in non-uniform image quality. Although there have been some methods proposed to reduce the heel effect [ 19 , 20 , 21 ], no suitable method has been presented that can objectively quantify the overall and non-uniform image quality caused by the heel effect. This study designed a CSW phantom for quantification of overall and non-uniform image quality in X-ray radiographs using nMI metrics based on information theory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the heel effect significantly impacted the signal-to-noise ratio (SNR) using an anthropomorphic phantom, but the image quality was not significantly different between pelvic radiographs with the head towards the anode and cathode directions [ 17 , 18 ]. Moreover, some previous studies performed post-processing heel effect correction (HEC) to minimize the inhomogeneous intensity in radiographs [ 19 , 20 , 21 ]. However, no suitable method has been presented that can objectively quantify the non-uniform image quality in radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the heel effect is corrected only for the gain-map composition and not for clinical images, which implies that intrinsic heel effect remains in clinical images even after the gain and offset correction. Regarding moving geometry, Yu and Wang 13 recently introduced a novel method to correct the heel effect for gain calibration in an SID-variant environment. Compared to their work, gain calibration for our system has different challenges, including 2D DOF of panel movement and the existence of the intrinsic obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…In Fig. 12(b), because the vignetting parts still have faint images, we can use a flat-field correction (FFC) method to correct these parts [25]. After that, we trim the partial images.…”
Section: Image Processingmentioning
confidence: 99%